Family physicians’ knowledge, beliefs, and practices in promoting healthy lifestyles and weight management for obese patients in Tabuk, Saudi Arabia - Alatawi, Amirah M.; Alanazi, Mansuor A.; Almohammadi, Maram Ati (Frontiers in Endocrinology, 2024)
Background Obesity is one of the most prevalent and relevant health problems in Saudi Arabia and requires urgent attention. Family physicians are the first point of contact and one of the most important starting points for the successful treatment of being overweight or obese. Aim This study aimed to assess the knowledge, beliefs, and practices of primary care physicians in promoting healthy lifestyles and physical activity among obese patients. Methods This cross-sectional study included family physicians who were board-certified or registered in a family medicine training program and working at government family healthcare centers in Tabuk. A predesigned structured questionnaire was distributed either in a printed form or as an online survey. Results The study included 83 family physicians. Of these, 84.1% agreed that overweight and obese patients should be screened for dyslipidemia, and 67.5% agreed to offer advice on weight control even if the patient did not ask for it, demonstrating what family medicine physicians thought of physical inactivity (97.6%). Assessment of the obesity counseling practices of family medicine physicians revealed that approximately three-fourths (75.9%) always calculated the body mass index (BMI) of patients during obesity management, while comprehensive counseling regarding physical activity was higher (81.9%). The system for providing educational materials as part of managing overweight or obesity was found to be inadequate as 25.3% had never done so. The family medicine physicians had sufficient knowledge and positive beliefs about obesity management but also improper counseling practices. A lack of training and poor patient compliance with management plans are the main barriers to controlling obesity levels.